Spectrum of interstitial lung diseases at a tertiary center in a developing country: A study of 803 subjects - Dhooria, Sahajal; Agarwal, Ritesh; Sehgal, Inderpaul Singh; Prasad, Kuruswamy Thurai; Garg, Mandeep; Bal, Amanjit; Aggarwal, Ashutosh Nath; Behera, Digambar (PloS one, 2018)
The spectrum of interstitial lung diseases (ILDs) have mainly been reported from the developed countries; data from developing countries is sparse and conflicting. The aim of this study is to describe the distribution of various ILDs from a developing country. This is an analysis of prospectively collected clinical, radiological and histological data of consecutive subjects (age >12 years) with ILDs from a single tertiary care medical center. The diagnosis of the specific subtype of ILD was made according to standard criteria for various ILDs. A total of 803 subjects (mean age, 50.6 years; 50.2% women) were enrolled between March 2015 to February 2017 of which 566 (70.5%) were diagnosed during the study period (incident cases). Sarcoidosis (42.2%), idiopathic pulmonary fibrosis (IPF, 21.2%), connective tissue disease (CTD)-related ILDs (12.7%), hypersensitivity pneumonitis (10.7%), and non-IPF idiopathic interstitial pneumonias (9.2%) were the most common ILDs. The spectrum of ILDs was not significantly different (p = 0.87) between incident and prevalent cases. A histopathological specimen was obtained in 49.9% of the subjects yielding a histologically confirmed diagnosis in 40.6%. A diagnostic procedure was not performed in 402 subjects; the most common reasons were presence of definite usual interstitial pneumonia pattern on high resolution computed tomography and patients' unwillingness to undergo the procedure. Sarcoidosis, IPF and CTD-ILDs were the most common ILDs seen at a tertiary center in northern India similar to the spectrum reported from developed countries. More studies are required from developing countries to ascertain the spectrum of ILDs in different geographic locales.